Ion bean etching on ti-30ta alloy for biomedical application - Capellato, Patricia [UNESP] (2015)
Titanium and titanium alloys are currently being used for clinical biomedical applications due to their high strength, corrosion resistance and elastic modulus. However, these materials have recently been shown to exhibit ion release and poor physiological integration that may result in fibrous encapsulation and further biomaterial rejection. In order to be a successful replacement for bone current approaches for enhancing the mechanical and biological properties of Ti was alloyed Ti with Ta due to it provides greatly improved mechanical properties which include fracture toughness and workability. Studies have shown techniques such ion beam etching, heat and alkaline treatment, SBF coatings and anodization to promote altered cellular response on Ti and Ti- alloys. In this study Ti-30Ta alloy was investigated ion beam etching. The SEM was used to investigate the topography, EDS the chemical composition, and surface energy was evaluate with contact angle analyze due to the topography have effect on protein adsorption, platelet adhesion, blood coagulation and bacterial adhesion. This study concludes Ti-30Ta alloy substrate with ion beam etching was not favorable for biomedical application.